129k views
4 votes
Where are the asymptotes of f(x) = tan(2x − π) from x = pi over 2 to x = 3 pi over 2?

A) x = 3 pi over 4, x = 5 pi over 4
B) x = 0, x = π, x = 2π
C) x = 0, x = pi over 4
D) x = pi over 2, x = 3 pi over 2

2 Answers

4 votes

1

Danios

High SchoolMathematics 5+3 pts

Where are the asymptotes of f(x) = tan(2x − π) from x = pi over 2 to x = 3 pi over 2?

A) x = 3 pi over 4, x = 5 pi over 4

B) x = 0, x = π, x = 2π

C) x = 0, x = pi over 4

D) x = pi over 2, x = 3 pi over 2

Comments (1) FollowReport by Danios 15.06.2018

hmmm those choices seem to include values outside the provided range, no? I mean, the provided range is [ π/2 , 3π/2 ], only the 2nd and 3rd Quadrants.

Ask Danios about this question...

Answers

Chaptown · Ambitious

Know the answer? Add it here!

Professor1994 Virtuoso

Answer: Option A) x=3π/4, x=5π/4

The asymptotes of the function tan (z) are the values of z that are the odd multiples of π/2:

z=(2n+1)π/2, witn n= ..., -3, -2, -1, 0, 1, 2, 3, ...

In this case z=2x − π, then:

2x − π=(2n+1)π/2

Solving for x: Adding π both sides of the equation:

2x − π+ π=(2n+1)π/2+ π

Adding the terms on the right side of the equation:

2x=[(2n+1)π+2π]/2

Common factor π:

2x=[(2n+1)+2]π/2

2x=(2n+1+2)π/2

2x=(2n+3)π/2

Multiplying both sides of the equation by 1/2:

(1/2)(2x)=(1/2)[(2n+3)π/2]

(2/2)x=(2n+3)π/[(2)(2)]

x=(2n+3)π/4

For n=-1:

x=[2(-1)+3]π/4

x=(-2+3)π/4

x=π/4

x=π/4<π/2 No

For n=0:

x=[2(0)+3]π/4

x=(0+3)π/4

x=3π/4

π/2<x=3π/4<3π/2 Ok

For n=1:

x=[2(1)+3]π/4

x=(2+3)π/4

x=5π/4

π/2<x=5π/4<3π/2 Ok

For n=2:

x=[2(2)+3]π/4

x=(4+3)π/4

x=7π/4

x=7π/4>3π/2 No

Answer: x=3π/4, x=5π/4

User Cademan
by
5.7k points
3 votes
Answer: Option A) x=3π/4, x=5π/4

The asymptotes of the function tan (z) are the values of z that are the odd multiples of π/2:
z=(2n+1)π/2, witn n= ..., -3, -2, -1, 0, 1, 2, 3, ...

In this case z=2x − π, then:
2x − π=(2n+1)π/2

Solving for x: Adding π both sides of the equation:
2x − π+ π=(2n+1)π/2+ π

Adding the terms on the right side of the equation:
2x=[(2n+1)π+2π]/2

Common factor π:
2x=[(2n+1)+2]π/2
2x=(2n+1+2)π/2
2x=(2n+3)π/2

Multiplying both sides of the equation by 1/2:
(1/2)(2x)=(1/2)[(2n+3)π/2]
(2/2)x=(2n+3)π/[(2)(2)]
x=(2n+3)π/4

For n=-1:
x=[2(-1)+3]π/4
x=(-2+3)π/4
x=π/4
x=π/4<π/2 No

For n=0:
x=[2(0)+3]π/4
x=(0+3)π/4
x=3π/4
π/2<x=3π/4<3π/2 Ok

For n=1:
x=[2(1)+3]π/4
x=(2+3)π/4
x=5π/4
π/2<x=5π/4<3π/2 Ok

For n=2:
x=[2(2)+3]π/4
x=(4+3)π/4
x=7π/4
x=7π/4>3π/2 No

Answer: x=3π/4, x=5π/4
User Red Virus
by
5.3k points